Government Policy in Establishing an Against a Core Youth Cadre Organization Against Drugs (KIPAN) West Java - Depi Mahdalena (GoResearch - Research & Publishing House, 2022)
Narcotics abuse is a crime that has entered the Disaster phase in Indonesia. West Java Province is included in the list of provinces in Indonesia with the fourth largest drug crime case rate with a total of 2,494 cases. In addition, you can also see data showing data on drug crime cases in West Java by age group. The purpose of this study is to find out how the evaluation is carried out by the West Java National Narcotics Agency in handling narcotics addicts in West Java. Evaluation is a way to assess the extent to which a policy can run according to the goals to be achieved. This study used a qualitative method with a literature study and documentation study approach. evaluation put forward by Milstein to evaluate the handling of narcotics addicts by the National Narcotics Agency of West Java Province.